2008
DOI: 10.1007/s10669-008-9165-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spent engine oil on the growth parameters and chlorophyll content of Corchorus olitorius Linn

Abstract: The effect of spent engine oil on the height, leaf number, leaf area, stem girth, chlorophyll, and mois-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 6 publications
4
31
0
Order By: Relevance
“…In both the experiments, the contaminant was added directly to the soil, with no time interval between the contamination and planting. Adenipekun et al (2008) concluded that the shorter length of seedlings of Corchorus olitorius L. (Tilicaceae) in the soil contaminated with oil was caused by the reduced water availability in the soil. According to Hester and Mendelssohn (2000), the growth of the plants could be hindered by the physical and chemical alterations in the soil caused by oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the experiments, the contaminant was added directly to the soil, with no time interval between the contamination and planting. Adenipekun et al (2008) concluded that the shorter length of seedlings of Corchorus olitorius L. (Tilicaceae) in the soil contaminated with oil was caused by the reduced water availability in the soil. According to Hester and Mendelssohn (2000), the growth of the plants could be hindered by the physical and chemical alterations in the soil caused by oil.…”
Section: Discussionmentioning
confidence: 99%
“…The same substance can induce different effects in different species, and conversely, the same symptoms can arise from exposure to different substances (Baker, 1970). The most common and important symptoms observed in the plants contaminated with oil and its byproducts include the erosion of the epicuticular wax (Baker, 1970), degradation of chlorophyll (Baker, 1970;Malallah et al, 1996 and, alterations in the stomatal mechanism (Baker, 1970), reduction in photosynthesis and respiration (Baker, 1970), increase in the production of stress-related phytohormones (Larcher, 2000), accumulation of toxic substances or their byproducts in vegetal tissue (Baker, 1970), decrease in size and less production of biomass (Proffitt et al, 1995;Green et al, 1996;Kuhn et al, 1998;Brandt et al, 2006;Daniel-Kalio and Pepple, 2006;Adenipekun et al, 2008). In some cases after an oil spill, an increase in the production of biomass and in the growth and development of some species can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in leaf area of eophylls in contaminated and bioremediated soils, with reduction in thickness, is contrary to what was reported for most plants studied, such as Amaranthus hybridus (Omosun et al 2008), Corchorus olitorius L. (Adenipekun et al (2009) and Mimosa pilulifera (Inckot et al 2008). In general, reduction in leaf area is attributed to water stress caused by the contaminant (Maranho et al 2006;Adenipekun et al 2008Adenipekun et al , 2009). As A. edulis exhibited an increase in leaf area of eophylls and alteration in the size of epidermic cells, it is believed that water stress was minimized by the quick response of the plant, with root branching and formation of root hairs.…”
Section: Discussionmentioning
confidence: 77%
“…Some species in petroleum-contaminated soil exhibited reduction in root-cell divisions (Achuba 2006), reduction in the meristematic region (Inckot et al 2008), alterations in the structure of root hairs (Alkio et al 2005), reduction in leaf area, changes in stomatal density (Adenipekun et al 2008), and in the aspect and thickness of the epicuticular wax (Omosun et al 2008), among other alterations.…”
Section: Nogueira L Et Almentioning
confidence: 99%
See 1 more Smart Citation